Antimicrobial Effect of Malaysian Honey on Some Human Pathogens: an in vitro Study - AT, Hassanain; AK, Alyaa; AJ, Karim (IIUM Medical Journal Malaysia, 2010)
Introduction: Honey has potent bactericidal activity against many pathogenic organisms, including various Gram-negative and Gram-positive bacteria. This study aimed to determine the antimicrobial effect of Malaysian honey against different species of human pathogens using optimized honey broth media. Materials and Methods: The antimicrobial activity of honey against standard strains of Gram-negative and Grampositive bacteria and yeast was tested in vitro by the broth dilution method using 10%-100% w/v concentrations prepared in tryptic soy broth. Results: Streptococcus pyogenes was the most sensitive pathogen, it was completely inhibited by 30% honey broth medium. The most resistant were E. faecalis, S. aureus and MRSA, but they were all completely inhibited by 80% honey broth medium. Conclusion: Honey is shown to possess antimicrobial activity against human Gram-positive and negative medically important bacteria.